Pride and the city - Philip S. Morrison (REGION, 2016)
Urban pride is an individual and collective response to living in a given city. Unlike other emotions such as life satisfaction or happiness with which it is weakly positively correlated, pride involves stake holding; to be proud of something requires having an investment in its success emotionally, financially or culturally. For this study I specify a multilevel model based on responses to a five category survey question which asks residents how proud they are in the "look and feel of their city". Responses to the 2008 survey are distributed over almost 6000 residents across 12 cities in New Zealand. Although the primary variation is among individuals, urban pride also varies by city and I show how differences in urban context affect the way different types of stake holding temper urban pride.
Keywords: R19; R59; I39; H89; 330; pride; urban pride; city; community; social identity; Quality of Life Survey; New Zealand